Producing knowledge or building 'regimes' of truth? : a critical study of two community based organisations and a development facilitation Agency in the Western Cape - Boswell, Rosabelle (Social Anthropology, 2016)
This study is based on research carried out at the request of the Community and Urban Services Support Project (CUSSP). The research formed part of the internship programme for the Practical Anthropology course at the University of Cape Town, and involved an investigation into the communication strategies employed by community based organisations in two selected areas in the Western Cape, namely, Franschhoek and New Rest (Guguletu). The thesis is a self-reflexive account of the research period and it explores how the acceptance of participatory approaches to development, and, conflicting interpretations of the term 'participation' can be constructed, maintained and reproduced; resulting in potential conditions which support processes of domination. Reflexivity involves a systematic and continuous analysis of the research process. To do this one should not necessarily aim to learn more about oneself (although this is an inevitable result of field work) but continuously to move from the 'intensely personal experience of one's own social interactions ... to the more distanced analysis of that experience for an understanding of how identities are negotiated, and [particularly for this thesis] how social categories, boundaries and hierarchies and processes of domination are experienced and maintained' (Wright & Nelson 1995:48).